An intervention to improve social participation for adolescents with autism spectrum disorder: Pilot study. (7th November 2013) - Goldingay, Sophie; Stagnitti, Karen; Sheppard, Loretta; McGillivray, Jane; McLean, Belinda; Pepin, Genevieve
Abstract: Objective : To increase flexible thinking, self-regulation and empathy for adolescents with ASD. Method : Five adolescents (M = 13.5 years; SD = 0.84 years; four males) were assessed pre and post intervention for flexible thinking and social competence (as measured by the SSIS). Parents rated their adolescent's social competence pre and post intervention. Results : A large decrease was found in parent rating of their child's level of hyperactivity (12.8, SD = 2.3; 11, SD = 2.2) ( p  = 0.034) (Cohen's d  = 0.95). Parents increased their rating of their child's cooperation and empathy (Cohen's d  = 0.71 and 0.56, respectively). A medium effect for flexible thinking was observed in three items (Cohen's d  = 0.5 to 0.62) and a large effect for one item (Cohen's d  = 1.35). Adolescents decreased self-scoring on the social scale post intervention. Conclusion : Improvements were observed in adolescents' flexible thinking and social insights, and parent's perception of their child's self-regulation.